2014
DOI: 10.1159/000362142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Retrotransposon with Sex Chromosome-Specific Distribution in <b><i>Silene latifolia</i></b>

Abstract: Silene latifolia is a dioecious plant species with chromosomal sex determination. Although the evolution of sex chromosomes in S. latifolia has been the subject of numerous studies, a global view of X chromosome structure in this species is still missing. Here, we combine X chromosome microdissection and BAC library screening to isolate new X chromosome-linked sequences. Out of 8 identified BAC clones, only BAC 86M14 showed an X-preferential signal after FISH experiments. Further analysis revealed the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Because other retrotransposons with similar chromosomal pattern have even more Y-linked copies according to FISH experiments, the computation cannot be used for their copy number estimation – resulting copy number of X-linked TE copies would be undervalued in that case. Figure 1e and results of previous publications [ 4 , 31 , 32 ] examining the chromosomal localization of repeats (Table 2 ) suggest that at least Ty3/Gypsy LTR retrotransposons AthilaCL3, OgreCL6, and RetandCL9 also spread predominantly through female lineage but their recent retrotransposition activity is rather low in most ecotypes.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Because other retrotransposons with similar chromosomal pattern have even more Y-linked copies according to FISH experiments, the computation cannot be used for their copy number estimation – resulting copy number of X-linked TE copies would be undervalued in that case. Figure 1e and results of previous publications [ 4 , 31 , 32 ] examining the chromosomal localization of repeats (Table 2 ) suggest that at least Ty3/Gypsy LTR retrotransposons AthilaCL3, OgreCL6, and RetandCL9 also spread predominantly through female lineage but their recent retrotransposition activity is rather low in most ecotypes.…”
Section: Resultssupporting
confidence: 55%
“…Although this hypothesis seems to be likely, our data also favor an additional explanation that retrotransposons tend to spread more in the maternal line than in the paternal, resulting in a low frequency of insertions into the Y chromosome and its lack of growth over the rest of the genome. This phenomenon was initially observed by cytogenetic analyses when it was found that several LTR retrotransposons show a lower hybridization signal on the Y chromosome of S. latifolia [ 4 , 8 , 32 , 53 ] and R. acetosa [ 5 ].…”
Section: Discussionmentioning
confidence: 97%
“…The large size of the C. grandis Y chromosome is mainly due to the accumulation of five TEs, one satellite and an unclassified repeat Genomic in silico analyses combined with in situ detection in plants with heteromorphic sex chromosomes have now been carried out in three species of flowering plants: S. latifolia (Cermak et al, 2008;Macas et al, 2011;Kralova et al, 2014;Steflova et al, 2014), R. acetosa (Steflova et al, 2013(Steflova et al, , 2014 and C. grandis (this study). Given that the difference between the male and female genomes of C. grandis is about 10% of the genome (Sousa et al, 2013), our chance of detecting Y-specific repeats was similar to that of a study of S. latifolia, where the Y chromosome also represents about 10% of the total genome (Macas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of retrotransposons is often responsible for the enormous size of evolutionarily young plant Y chromosomes. Various families of retrotransposons contribute unequally to the size of the X and Y chromosomes in R. acetosa and S. latifolia [ 18 , 30 , 35 , 36 , 37 ], and the proliferation of individual retrotransposons may significantly vary between closely related species with and without sex chromosomes, as was shown in S. latifolia and S. vulgaris [ 38 ] as well as in Asparagus [ 39 , 40 ]. Transposable elements thus have a strong influence on the genome architecture of evolving sex chromosomes.…”
Section: Transposable Elements—major Force In Sex Chromosome Dynammentioning
confidence: 99%
“…Although some TEs prefer insertion into specific chromosomal regions such as subtelomeres, microsatellite loci [ 41 ], other transposons [ 42 ], or gene promoters [ 43 ], which probably evolved to prevent insertion into protein coding genes, most plant TEs are randomly distributed along chromosomes with different density on sex chromosomes compared to autosomes. This phenomenon is widespread and applies to the majority of highly abundant TEs in S. latifolia and R. acetosa [ 18 , 30 , 35 , 36 , 37 ]. Figure 3 shows a schematic representation of idealized chromosomal distributions of Long Terminal Repeat (LTR) retrotransposons in dioecious plants and a hypothetical causal mechanism; i.e., restricted TE proliferation in either male or female reproductive organs.…”
Section: Transposable Elements—major Force In Sex Chromosome Dynammentioning
confidence: 99%